Antibacterial Activity of Nanocomposite Chitosan-Silver Nanoparticle with Cymbopogon citratus Extract as a Bioreductor Against Staphylococcus aureus - Rezky Anggraeni; Ananda Shelly Melyda; Alfred Pakpahan; Dewi Ranggaini; Johni Halim; Komariah Komariah (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
Nanocomposites are materials formed by combining two components, one or both of which are on the nanometer scale. The nanocomposite in this study is a combination of chitosan and silver nanoparticles produced through the synthesis of silver nitrate using Cymbopogon citratus extract. Silver nanoparticles have antibacterial abilities that can be utilized to overcome various diseases. However, their antibacterial properties may be reduced due to the tendency of silver nanoparticles to agglomerate. This can be overcome by the addition of chitosan as a stabilizing agent to prevent agglomeration and maintain the antibacterial effectiveness of silver nanoparticles. This study aims to evaluate the antibacterial activity of a nanocomposite formed by combining chitosan and silver nanoparticles synthesized using Cymbopogon citratus extract against Staphylococcus aureus through the diffusion method. The samples used included nanocomposites at concentrations of 6.25 mg/mL, 12.5 mg/mL, 15 mg/mL, 25 mg/mL, and 50 mg/mL, amoxicillin as a positive control, Acetic acid, and distilled water as negative controls. The results of antibacterial activity testing showed that all nanocomposite test concentrations had the ability to inhibit the growth of Staphylococcus aureus as evidenced by the formation of an inhibition zone around the disc paper. However, the highest antibacterial activity shown by the nanocomposites was still lower compared to the antibacterial activity of amoxicillinÂ Keywords: Antibacterial activity, Chitosan, Cymbopogon citratus, Silver nanoparticles, Staphylococcus aureus